Al-Quran themes classification using ontology - Ta'a, Azman; Zainal Abidin, Syuhada; Abdullah, Mohd Syazwan; Mat Ali, Abdul Bashah; Ahmad, Muhammad (2012)
Knowledge representations of Al-Quran involved the classification of contents for understanding the readers.In information technology environment, the representation and classification approaches must be understood by human and computer in order to ensure the correct semantics of Al-Quran knowledge.Current approaches used conventional methods such as taxonomy, hierarchy or tree structure, which only provides a concept definition without linked to another possibility of knowledge explanation.This research aims to explore the approach to represent and classify the Al-Quran knowledge by using ontology.The ontology model for Al-Quran is developed according to the themes of Al-Quran knowledge as described in Syammil Al-Quran Miracle the Reference.The ontology approach has shown that the Al-Quran knowledge can be classified and presented to the readers systematically. Moreover, the ontology structure that representing the relationships among the theme concepts in Al-Quran was reviewed and validated by the domain experts in Al-Quran.